TEOLOGI INKLUSIVISME KARL RAHNER: IMPLIKASI BAGI PENDIDIKAN IMAN DAN TRANSFORMASI KEKRISTENAN - Sipahutar, Antonius P; Putranias Zebua; Anisa Putri Hulu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the theology of inclusivism of Karl Rahner, which is rooted in the understanding of God’s grace as universal, yet remains centered on Christ as the culmination of divine revelation. This study aims to analyze how Rahner’s inclusivism interprets salvation in the context of religious pluralism and its implications for the transformation of Christian life and the development of faith education. This study employs a qualitative method with a library research approach, using descriptive-critical analysis of Rahner’s works, interreligious theological literature, and studies on the praxis of Church life. Theological literature in Indonesia remains limited in addressing Rahner, particularly regarding the implementation of inclusivism in Church practices and faith education; therefore, this study seeks to fill this gap. The findings of this study indicate that Rahner’s understanding of universal grace enables the Church to maintain its Christological identity while fostering a dialogical attitude in a pluralistic society. This perspective provides a theological foundation for the transformation of Church praxis and faith education, which emphasizes not only the transmission of doctrine but also the formation of an openness of faith toward human experience and the reality of religious pluralism.